2015
DOI: 10.5588/ijtld.15.0341
|View full text |Cite
|
Sign up to set email alerts
|

Patients' costs associated with seeking and accessing treatment for drug-resistant tuberculosis in South Africa

Abstract: Summary Setting South Africa is one of the world’s 22 high tuberculosis (TB) burden countries, with the second highest number of notified rifampicin-resistant TB (RR-TB) and multidrug-resistant TB (MDR-TB) cases. Objective To estimate patient costs associated with the diagnosis and treatment of RR-TB/MDR-TB in South Africa. Design Patients diagnosed with RR-TB/MDR-TB and accessing care at government health care facilities were surveyed using a structured questionnaire. Direct and indirect costs associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
58
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(65 citation statements)
references
References 14 publications
(21 reference statements)
4
58
0
2
Order By: Relevance
“…First, the study was not nationally representative as it was carried out in five health facilities in two rural counties. Secondly, the use of an official minimum wage to estimate productivity loss for all patients could have potentially overestimated indirect costs among patients who were unemployed prior to their illness or underestimated indirect costs among those who were employed . Recall bias is a concern in patient cost surveys.…”
Section: Discussionmentioning
confidence: 99%
“…First, the study was not nationally representative as it was carried out in five health facilities in two rural counties. Secondly, the use of an official minimum wage to estimate productivity loss for all patients could have potentially overestimated indirect costs among patients who were unemployed prior to their illness or underestimated indirect costs among those who were employed . Recall bias is a concern in patient cost surveys.…”
Section: Discussionmentioning
confidence: 99%
“…We estimated the direct and indirect costs incurred by study participants while accessing care from the reported start of tuberculosis symptoms 21, 22. In summary, three samples of patients were interviewed 21 .…”
Section: Methodsmentioning
confidence: 99%
“…We interviewed a further cohort of 168 patients on first-line tuberculosis treatment, who were not part of the XTEND cohort (to protect from interview overload), at 2 months and 5 months from start of treatment. Finally, we interviewed a cross-section of 134 patients with multidrug-resistant tuberculosis from Western Cape 22 . All respondents were asked about their health-seeking activities, the associated costs, income loss, the time cost of carers, and any coping strategies used.…”
Section: Methodsmentioning
confidence: 99%
“…Although the Global Fund Tuberculosis Program and NRCMS may cover almost all direct MDR-TB treatment expenses, patients still have to pay for other related testing fees and may be affected by lost wages, transportation costs and other indirect economic losses. As most MDR-TB patients have been shown to be particularly impoverished, they may choose to not enroll in treatment [911], Additional reasons for non-enrollment in treatment are discussed below.…”
Section: Discussionmentioning
confidence: 99%